2021
DOI: 10.31880/10344/10209
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Taxonomy of Divestment. The Lifespan of Products as a Process

Abstract: This paper presents findings of research focused on the divestment of material possessions. It argues that divestment can be better understood as a process instead of a moment in the lifespan of a product. The term divestment refers to the process through which owners separate physically or emotionally from their possessions. Using qualitative data obtained through the Photo-Elicitation Interview method, the study explores the experiences of people on three types of items: clothing, furniture and mobile phone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In consumption research, the deterioration phase is known as divestment, a process people experience when separating from their belongings [13]. Similarly, divestment is not a straightforward process: each owner-product interaction is relevant and can contribute to accelerating, slowing down and even reversing the divestment [14]. Thus, despite the damage that conflict can inflict, wearers may still render the relationship salvageable.…”
Section: Our Relationship With Clothesmentioning
confidence: 99%
See 2 more Smart Citations
“…In consumption research, the deterioration phase is known as divestment, a process people experience when separating from their belongings [13]. Similarly, divestment is not a straightforward process: each owner-product interaction is relevant and can contribute to accelerating, slowing down and even reversing the divestment [14]. Thus, despite the damage that conflict can inflict, wearers may still render the relationship salvageable.…”
Section: Our Relationship With Clothesmentioning
confidence: 99%
“…For example, garments infrequently used due to avoidance or separation can decrease intimacy and commitment. In their study on product divestment, Encino-Muñoz et al identified irregular use as a point when items may be on the brim of physical divestment [14]. This is the moment when divestment can be prevented because use can contribute to the item's value [14].…”
Section: Dealing With Conflict In Wearer-clothing Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation